Multi-omics profiling identifies a deregulated FUS-MAP1B axis in ALS/FTD-associated UBQLN2 mutants - Strohm, Laura; Hu, Zehan; Suk, Yongwon; Rühmkorf, Alina; Sternburg, Erin; Gattringer, Vanessa; Riemenschneider, Henrick; Berutti, Riccardo; Graf, Elisabeth; Weishaupt, Jochen H.; Leischner-Brill, Monika; Harbauer, Angelika Bettina; et al. (Life science alliance, 2022)
Ubiquilin-2 (UBQLN2) is a ubiquitin-binding protein that shuttles ubiquitinated proteins to proteasomal and autophagic degradation. UBQLN2 mutations are genetically linked to the neurodegenerative disorders amyotrophic lateral sclerosis and frontotemporal dementia (ALS/FTD). However, it remains elusive how UBQLN2 mutations cause ALS/FTD. Here, we systematically examined proteomic and transcriptomic changes in patient-derived lymphoblasts and CRISPR/Cas9-engineered HeLa cells carrying ALS/FTD UBQLN2 mutations. This analysis revealed a strong up-regulation of the microtubule-associated protein 1B (MAP1B) which was also observed in UBQLN2 knockout cells and primary rodent neurons depleted of UBQLN2, suggesting that a UBQLN2 loss-of-function mechanism is responsible for the elevated MAP1B levels. Consistent with MAP1B's role in microtubule binding, we detected an increase in total and acetylated tubulin. Furthermore, we uncovered that UBQLN2 mutations result in decreased phosphorylation of MAP1B and of the ALS/FTD-linked fused in sarcoma (FUS) protein at S439 which is critical for regulating FUS-RNA binding and MAP1B protein abundance. Together, our findings point to a deregulated UBQLN2-FUS-MAP1B axis that may link protein homeostasis, RNA metabolism, and cytoskeleton dynamics, three molecular pathomechanisms of ALS/FTD.
Gesehen am 08.08.2022